ECOSYSTEM ANALYSIS BETWEEN TOURIST AND NON-TOURIST BEACHES: BASED ON THE COMMUNITY STRUCTURE OF Ocypode sp. - Lestariani, Nurlita; Zulfaeda, Aulia; Apriani, Najwa (Politeknik Kelautan dan Perikanan Karawang, BRSDM KP., 2025)
This research aims to analyze the differences between tourist and non-tourist beach ecosystems based on the community structure of Ocypode sp. Community analysis was carried out at two locations: Loang Baloq Beach (tourism) and Setangi Beach (non-tourism). The line-transect method was chosen for sample collection. At each location, three stations were created, and at each station, there were five quadrants. The water physico-chemical data collection consists of brightness, pH, temperature, TDS, and EC (conductivity). Apart from that, data was collected on human activity around the beach using certain criteria: 1) distance from the beach to the city center; 2) the existence of hotels or buildings around the beach; 3) the presence of physical waste; 4) visitor frequency; and 5) the existence of public facilities. Samples of Ocypode sp. were identified and then analyzed using density formulas, relative density, and diversity index. We found five species of ghost crab (Ocypode sp.) at Loang Baloq and Setangi Beach: Ocypode kuhlii, Ocypode jousseamei, Ocypode pallidula, Ocypode ryderi, and Ocypode japonica. The highest density and diversity of Ocypode sp. are found at Setangi Beach (non-tourist). The physico-chemistry of Setangi Beach waters shows better quality than Loang Baloq Beach. Likewise, the characteristics of human activity in the coastal area were observed. It can be concluded that physico-chemical factors and human activities influence the density and diversity of Ocypode sp. In addition, based on the community structure of Ocypode sp., it is stated that Setangi Beach (non-tourist) has better ecosystem quality than Loang Baloq Beach (tourism).